Use of low-cost daylighting system: Custom design and application consequences in an office environment - Ferron, Leandro Martin (2011)
Nowadays, many working environments are located within facilities that are not visually connected with the exterior. This is due to the new architectural paradigms as regards the design, based on the possibility to substitute natural light for artificial lighting even in daytime. Accordingly, the need of reducing energy costs and the user's wish to optimize lighting and visual comfort levels raises the option of innovative natural lighting systems implementation. For a luminous retrofitting case, located in Mendoza, Argentina, a specific methodology used determined that the more adequate natural lighting strategy would be redirecting direct sunlight, working on the reflected light design. The methodology proposed is formed by an analysis of the initial situation, conditions modelization and design resolving proposals, through luminous evaluation, real and virtual scale model construction, and performance evaluation using heliodon and simulation software. This work points to use natural lighting to reduce energy consumption and get better luminous ambient through the application of a low-cost daylighting system. In the mentioned case, strategies of redirection of the solar component capable of optimizing indoor lighting levels up to a 40% were applied.